Approaching person-centered clinical practice: A cluster analysis of older inpatients utilizing the measurements of intrinsic capacity - Wu, Wenbin; Sun, Liang; Li, Hong; Zhang, Jie; Shen, Ji; Li, Jing; Zhou, Qi (Frontiers in Public Health, 2022)
Background: Maintaining the intrinsic capacity (IC) of older inpatients is a novel view in providing person-centered treatments in clinical practice. Uncertainty remains regarding the primary nature of IC among older hospitalized patients. Objectives: We aimed to understand the status of IC among older inpatients by a cluster analysis based on IC measurements. Methods: This is a cross-sectional study conducted in the geriatric department of Beijing Hospital in China. Older inpatients who were over 60 years and performed comprehensive geriatric assessments were included. Inpatients were classified into subgroups using 13 measurements of IC according to unsupervised methods (K‐means cluster analysis and t-SNE). Subgroup differences were investigated for domains of IC, age, sex, frailty, activities of daily living, and falls. Results: A total of 909 inpatients with a mean age of 76.6 years were included. Almost 98% of the inpatients showed IC impairment. Locomotion impairment was the most prevalent problem (91.1%), followed by sensory impairment (61.4%), psychological impairment (57.3%), cognition decline (30.7%), and vitality problem (29.2%). Five clusters were obtained by classification: Cluster 1 (56.6% of participants) showed high IC with fair impairment of locomotion and vision; Cluster 2 and 3 (37.8 % of participants) had additional impairment of sleep in the psychological domain; Cluster 4 and 5 (5.6% of participants) represented a severe loss of all the IC domains; Clusters from 1 to 5 showed a gradual decline in the IC score and were significantly associated with increased age, frailty, decreased activities of daily living, and falls. Significant correlations between domains were observed; the locomotion domain showed the strongest links to the others in network analysis. Conclusions: Great declines in IC and disparities between IC domains were found in older inpatients. IC-based primary assessment and classification enabled us to identify the variation of functional abilities among older inpatients, which is pivotal for making integrated treatment or care models in clinical practice.